2014
DOI: 10.1007/s12223-014-0348-9
|View full text |Cite
|
Sign up to set email alerts
|

Enteric fever imported to the Czech Republic: epidemiology, clinical characteristics and antimicrobial susceptibility

Abstract: The aim of this study was to describe epidemiological and clinical characteristics of imported enteric fever in Czech travellers and to determine the antimicrobial susceptibility of isolated strains. Retrospective descriptive study included adult patients treated with enteric fever at Hospital Na Bulovce during January 2004-December 2012. A case of typhoid or paratyphoid fever was defined as isolation of Salmonella Typhi or Paratyphi from blood or stool. During the study period, there have been diagnosed 19 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(33 reference statements)
0
3
0
1
Order By: Relevance
“…Moreover,~66% of isolates in European countries [17], shows decreased susceptibility to ciprofloxacin, although it was considered in the past as first therapeutic choice [61] by the World Health Organization guidelines. In U.S., during 2016-2018, 5/29 cases of typhoid fever in patients who recently traveled to Pakistan were caused by extensively drug resistant strains [18].…”
Section: Antimicrobial Resistance and Typhoid Fevermentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover,~66% of isolates in European countries [17], shows decreased susceptibility to ciprofloxacin, although it was considered in the past as first therapeutic choice [61] by the World Health Organization guidelines. In U.S., during 2016-2018, 5/29 cases of typhoid fever in patients who recently traveled to Pakistan were caused by extensively drug resistant strains [18].…”
Section: Antimicrobial Resistance and Typhoid Fevermentioning
confidence: 99%
“…Similarly, a retrospective study conducted in Qatar, between 2005 and 2012, reported 356 cases of typhoid fever, of whom 96.9% had traveled abroad, mainly in the Indian subcontinent [17]. Over 70% of typhoid fever cases in Europe are acquired abroad and frequently caused by strains with marked antibiotic resistance profile [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Las medidas terapéuticas adicionales y la administración de antibióticos como las cefalosporinas de tercera generación por vía parenteral, basada en la sensibilidad del cultivo, deben continuarse hasta cinco días después de la recuperación. (41,42,43) AFECCIONES INFRECUENTES EN LA PRÁCTICA QUIRÚRGICA CAP. 3.…”
Section: Tratamiento Médicounclassified
“…Typhoid scenario in developed countries is usually associated with travelers returning from endemic countries. However, recent report con rmed alarming typhoid cases in developed countries associated with domestic sources and not linked with visit to endemic counties [2][3][4] . Typhoid fever is one of the etiologies for acute undifferentiated fever 5 .…”
Section: Introductionmentioning
confidence: 99%